2010
DOI: 10.1121/1.3280236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulus duration on amplitude modulation processing with cochlear implants

Abstract: This study investigated temporal integration processes underlying cochlear implant (CI) users’ amplitude modulation processing. Thresholds for modulation detection (AMDTs) and modulation frequency discrimination (AMFDTs) were measured for 50-, 100-, and 200-Hz modulation frequencies with stimulus durations from 50 to 400 ms in eight adult CI users. The results showed significant interactions between modulation frequency and stimulus duration for AMDTs and AMFDTs. The data suggest that temporal integration limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 17 publications
1
11
1
Order By: Relevance
“…A range of studies on amplitude modulation detection in CI users reported the effects of stimulation rate (Galvin & Fu 2005, 2009Pfingst et al 2007;McKay & Henshall 2010;Arora et al 2011), stimulation site (Pfingst et al 2007;Garadat et al 2012), stimulation mode (Galvin & Fu 2005;Pfingst 2011), stimulus duration (Luo et al 2010), stimulus level (Galvin & Fu 2005, 2009Pfingst et al 2007), and loudness growth (McKay & Henshall 2010) on AMDTs. In most of these studies, the electrical stimulus was presented directly to one or more electrodes using computer-controlled stimulation, bypassing the clinical sound processor.…”
Section: Introductionmentioning
confidence: 98%
“…A range of studies on amplitude modulation detection in CI users reported the effects of stimulation rate (Galvin & Fu 2005, 2009Pfingst et al 2007;McKay & Henshall 2010;Arora et al 2011), stimulation site (Pfingst et al 2007;Garadat et al 2012), stimulation mode (Galvin & Fu 2005;Pfingst 2011), stimulus duration (Luo et al 2010), stimulus level (Galvin & Fu 2005, 2009Pfingst et al 2007), and loudness growth (McKay & Henshall 2010) on AMDTs. In most of these studies, the electrical stimulus was presented directly to one or more electrodes using computer-controlled stimulation, bypassing the clinical sound processor.…”
Section: Introductionmentioning
confidence: 98%
“…With single electrodes and direct electric stimulation, a wide range of temporal modulation detection studies have been conducted including the evaluation of temporal modulation transfer functions (TMTFs) (e.g., Shannon, 1992;Busby et al, 1993), the determination of effects of stimulation rate, mode, level (Galvin and Fu, 2005), site (Pfingst et al, 2007(Pfingst et al, , 2008, loudness growth (Galvin and Fu, 2009), envelope masking (Chatterjee and Oba, 2004), and stimulus duration (Luo et al, 2010) on modulation detection thresholds (MDTs), the analysis of the relationship between amplitude modulation detection and intensity discrimination (Donaldson and Viemeister, 2000), and the effect of amplitude modulation on loudness perception (McKay and Henshall, 2010). This approach provides useful information about what electrical amplitude modulation CI users are capable of hearing, and suggest ways future technologies might make best use of these abilities.…”
Section: Introductionmentioning
confidence: 99%
“…At that level, the function had a steep roll-off at high AM rates (>200 Hz). At low AM rates, there was also a worsening of performance, perhaps owing to limited stimulus duration [i.e., not as many cycles of AM at low rates as at high rates within the 300 ms duration: see Luo et al (2010)]. This worsening of performance at low rates generally is not observed in AMD tasks.…”
Section: Introductionmentioning
confidence: 99%